Enfoques da educação ambiental voltados ao tema resíduos sólidos na Região do Grande ABC/SP: uma análise baseada na Política Nacional de Resíduos Sólidos - Alves, Patricia Martin [UNIFESP] (2017)
Solid waste generation in Brazil grew by 4.1% from 2012 to 2013, while the urban population growth rate in the same period was 3.7%. More than half of this amount is generated in the southeast region, being the São Paulo state the largest generator. The Greater ABC region, which is integrated by seven counties, also observed a greater increase in its consumption indices and solid waste generation in recent years, which does not exceed the rate of population growth. Thus, it is extremely important to incorporate practices of conscious consumption and questioning the current productive model, either through education or through the establishment of public policies in the area of solid waste. The National Solid Waste Policy proposes to incorporate more sustainable practices with the objective of non-generation, reduction, reuse, recycling and treatment of solid wastes, as well as adequate disposal of tailings. This study aimed to analyze the approaches given by the Public Power to Environmental Education focused on solid waste in the Greater ABC / SP region. The research has a descriptive character using as methods document analysis, semi-structured interview and content analysis of municipal solid wastes management plans and statistical data relating to generation and destination of residues, the semi-structured interview with the managers of Environmental Education and Solid Wastes from Grande ABC counties and content analisys of the printed materials of environmental education and also of the speeches of managers interviewed.The results demonstrate that the focus of the printed materials analyzed and the environmental education practices exemplified by the interviewed has a pragmatic character. It was also observed that the selective collection is the main theme to be treated in the Environmental Education of the cities evaluated. Regarding solid waste management, it was verified that all the counties participating in the research contemplate in their town plan the mandatory items proposed by Law 12305/2010. Important gaps were observed from the interviews with the managers / heads of Environmental Education and Solid Waste of the counties: inefficient reverse logistics, the problem of construction waste, technical staff and structure not compatible with demand.